A Brief Review on the Current Trends in Microencapsulation: Review Article (Journal of Pharma Insights and Research, 2024)
Microencapsulation has emerged as a pivotal technology in the field of novel drug delivery systems (NDDS), offering significant advantages in enhancing the efficacy, safety, and patient compliance of therapeutic agents. This cutting-edge technique involves encapsulating active pharmaceutical ingredients (APIs) within microscopic protective coatings, enabling controlled release, targeted delivery, and improved bioavailability. Microencapsulation has proven to be a versatile tool in addressing various pharmaceutical challenges, such as masking unpleasant tastes, protecting sensitive drugs from degradation, and modifying the absorption site of drugs. This comprehensive review aims to provide an in-depth understanding of microencapsulation, its principles, techniques, and diverse applications in the pharmaceutical industry. The article delves into the reasons for employing microencapsulation, including extended or sustained drug release, taste and odor masking, conversion of liquids into free-flowing powders, and stabilization of light, moisture, or oxygen-sensitive drugs. Additionally, the classification of microparticles based on their core and shell materials is discussed. Furthermore, the review explores the advantages and disadvantages of microencapsulation, highlighting its ability to protect encapsulated active agents, transform gases and liquids into solid particles, modify surface and colloidal properties, and alter the release profiles of drugs. Various microencapsulation techniques are extensively covered, including air suspension, coacervation phase separation, pan coating, spray drying and spray congealing, and solvent evaporation. The applications of microencapsulation span across diverse industries, such as pharmaceuticals, cosmetics, agrochemicals, and food. This review provides insights into the utilization of microencapsulated products in these sectors, emphasizing their role in enhancing product functionality, stability, and controlled release